Closed-kinetic chain upper-body training improves throwing performance of NCAA Division I softball players - Prokopy, M. P.; Ingersoll, C. D.; Nordenschild, E.; Katch, F. I.; Gaesser, G. A.; Weltman, A. (The Journal of Strength and Conditioning Research, 2008)
Closed-kinetic chain resistance training (CKCRT) of the lower body is superior to open-kinetic chain resistance training (OKCRT) to improve performance parameters (e.g., vertical jump), but the effects of upper-body CKCRT on throwing performance remain unknown. This study compared shoulder strength, power, and throwing velocity changes in athletes training the upper body exclusively with either CKCRT (using a system of ropes and slings) or OKCRT. Fourteen female National Collegiate Athletic Association Division I softball player volunteers were blocked and randomly placed into two groups: CKCRT and OKCRT. Blocking ensured the same number of veteran players and rookies in each training group. Training occurred three times weekly for 12 weeks during the team's supervised off-season program. Olympic, lower-body, core training, and upper-body intensity and volume in OKCRT and CKCRT were equalized between groups. Criterion variables pre- and posttraining included throwing velocity, bench press one-repetition maximum (1RM), dynamic single-leg balance, and isokinetic peak torque and power (PWR) (at 180[degrees][middle dot]s-1) for shoulder flexion, extension, internal rotation, and external rotation (ER). The CKCRT group significantly improved throwing velocity by 2.0 mph (3.4%, p < 0.05), and the OKCRT group improved 0.3 mph (0.5%, NS). A significant interaction was observed (p < 0.05). The CKCRT group improved its 1RM bench press to the same degree (1.9 kg) as the OKCRT group (p < 0.05 within each group). The CKCRT group improved all measures of shoulder strength and power, whereas OKCRT conferred little change in shoulder torque and power scores. Although throwing is an open-chain movement, adaptations from CKCRT may confer benefits to subsequent performance. Strength coaches can incorporate upper-body CKCRT without sacrificing gains in maximal strength or performance criteria associated with an athletic open-chain movement such as throwing.